2014
DOI: 10.1021/jf501117p
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Immunoglobulin E (IgE) Binding to Cashew Allergens following Sodium Sulfite Treatment and Heating

Abstract: Cashew nut and other nut allergies can result in serious and sometimes life-threatening reactions. Linear and conformational epitopes within food allergens are important for immunoglobulin E (IgE) binding. Methods that disrupt allergen structure can lower IgE binding and lessen the likelihood of food allergy reactions. Previous structural and biochemical data have indicated that 2S albumins from tree nuts and peanuts are potent allergens, and that their structures are sensitive to strong reducing agents such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…Sulfites are multipurpose compounds found as calcium, potassium, or sodium salts in food and pharmaceutical industries as preservatives or antioxidants. They are also used to slow food oxidation and can sometimes affect the smell and taste of foods (3,4).…”
Section: Page 3 Of 27mentioning
confidence: 99%
“…Sulfites are multipurpose compounds found as calcium, potassium, or sodium salts in food and pharmaceutical industries as preservatives or antioxidants. They are also used to slow food oxidation and can sometimes affect the smell and taste of foods (3,4).…”
Section: Page 3 Of 27mentioning
confidence: 99%
“…Rabbit anti-cashew antibody [34] was diluted 1:1000 in PBST and incubated for 1 h at room temperature.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Hypoallergenic formulas based on hydrolyzed milk proteins for infants with cow's milk allergy are commercially available since 1985. Recent laboratory studies have shown potential hypoallergenicity of peanut-polyphenol edible matrix [62] and cashew allergens treated with sodium sulfite in a temperature-dependent manner [63].…”
Section: Allergen Detectionmentioning
confidence: 99%